2020
DOI: 10.1186/s12890-020-1050-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of bronchiectasis in Italy

Abstract: Background The understanding of the epidemiology of bronchiectasis is still affected by major limitations with very few data published worldwide. The aim of this study was to estimate the epidemiological burden of bronchiectasis in Italy in the adult population followed-up by primary care physicians. Methods This study analyzed data coming from a large primary care database with 1,054,376 subjects in the period of time 2002–2015. Patients with bronchiectasis were selected by the use of International Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 19 publications
2
39
0
1
Order By: Relevance
“…Despite a relatively higher incidence of bronchiectasis in South Korea compared with Western countries, we showed that the incidence of bronchiectasis in South Korea decreased annually along with the incidence of TB. These results are surprising considering the increasing incidence of bronchiectasis in Western countries, in which the TB prevalence has remained continuously low [10,11]. We further evaluated common aetiologies of bronchiectasis other than TB.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Despite a relatively higher incidence of bronchiectasis in South Korea compared with Western countries, we showed that the incidence of bronchiectasis in South Korea decreased annually along with the incidence of TB. These results are surprising considering the increasing incidence of bronchiectasis in Western countries, in which the TB prevalence has remained continuously low [10,11]. We further evaluated common aetiologies of bronchiectasis other than TB.…”
mentioning
confidence: 92%
“…We previously reported that the prevalence of bronchiectasis in South Korea was 464 cases per 100 000 population, which was higher than that reported in Western countries [ 1 ]. This study showed that the annual incidences of bronchiectasis were 147–229 cases per 100 000 population, which was a higher rate than the 29 cases per 100 000 population recorded in the USA [ 9 ], 21 cases per 100 000 population observed in Germany [ 10 ], and 16 cases per 100 000 population observed in Italy [ 11 ]. Despite a relatively higher incidence of bronchiectasis in South Korea compared with Western countries, we showed that the incidence of bronchiectasis in South Korea decreased annually along with the incidence of TB.…”
mentioning
confidence: 99%
“…Patients with bronchiectasis often suffer from persistent respiratory symptoms, decreased quality of life, and recurrent respiratory infection 1 . As the prevalence of bronchiectasis 2 7 and associated health costs 2 , 8 , 9 is increasing in many countries, this disease is becoming an emerging threat to global health 10 , 11 . However, unfortunately, these expectations are based on studies performed mostly in Western countries 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…4 The prevalence of bronchiectasis appears to be increasing, though true prevalence may be influenced by other factors such as improved diagnosis using HRCT and inaccurate diagnosis due to comorbidities. [5][6][7][8][9] The aim of therapeutic management is to break the recurrent cycle of inflammation and infection, to preserve lung function, reduce exacerbations and complications, and improve health-related quality-of-life. 10 11 Antibiotics are the frontline therapy for bronchiectasis and most international guidelines also recommend airway clearance techniques (ACT) and pulmonary rehabilitation (PR).…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane systematic review of self-management interventions found insufficient evidence to assess the benefits for patients with bronchiectasis 17 and added to the call for research to define and develop these interventions. 9 10 18 The aim of this study was to explore views of self-management with key stakeholders to inform the design and development of future self-management programmes.…”
Section: Introductionmentioning
confidence: 99%